2005
DOI: 10.4049/jimmunol.175.4.2278
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ganglioside Antigen Identified by B Cells in Human Medullary Breast Carcinomas: The Proof of Principle Concerning the Tumor-Infiltrating B Lymphocytes

Abstract: The potential tumor-recognizing capacity of B cells infiltrating human breast carcinoma is an important aspect of breast cancer biology. As an experimental system, we used human medullary breast carcinoma because of its heavy B lymphocytic infiltration paralleled to a relatively better prognosis. Ig-rearranged V region VH-JH, Vκ-Jκ, and Vλ-Jλ genes, amplified by RT-PCR of the infiltrating B cells, were cloned, sequenced, and subjected to a comparative DNA analysis. A combinatorial single-chain variable fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 59 publications
5
47
0
Order By: Relevance
“…Characterization of TIL B cells of infiltrating ductal carcinoma revealed that these cells have undergone clonal expansion and isotype switching and have accumulated somatic mutations (15,16). Recombinant Igs derived from medullary breast carcinoma B cell infiltrates were shown to bind a ganglioside present in several breast cancer cell lines (25). This strongly suggests that, at least some, of the infiltrating B cells are driven by a specific tumor Ag.…”
Section: The Role Of Tumor-infiltrating B Cellsmentioning
confidence: 95%
“…Characterization of TIL B cells of infiltrating ductal carcinoma revealed that these cells have undergone clonal expansion and isotype switching and have accumulated somatic mutations (15,16). Recombinant Igs derived from medullary breast carcinoma B cell infiltrates were shown to bind a ganglioside present in several breast cancer cell lines (25). This strongly suggests that, at least some, of the infiltrating B cells are driven by a specific tumor Ag.…”
Section: The Role Of Tumor-infiltrating B Cellsmentioning
confidence: 95%
“…To date, very few targets of antibodies produced by B cells located within a tumor have been directly identified. Kotlan et al [23] constructed an scFv library from IgG variable chain genes derived from human medullary breast carcinomainfiltrating B lymphocytes and isolated an scFv that binds to gangliosides, which had been previously identified as TAAs. Also, Yasuda et al [42] engrafted human lung tumor tissue in SCID mice and identified antibodies to mutated p53 in the mouse serum.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of B cells from tumors and metastatic lymph nodes found hypermutated antibody genes and expansion of class-switched memory cells and plasmablasts in patients with bladder cancer [17]. Intratumoral germinal centers (GCs) have been reported to be present in NSCLC [18][19][20], breast cancer [21][22][23][24], colon cancer [25], and germ cell cancers [26]. In NSCLC, GCs are associated with early-stage disease [19], suggesting that a humoral immune response may hold these tumors in check.…”
mentioning
confidence: 99%
“…These dual effects may be due to the tumor cells and/or the inflammatory context. The case of B lymphocytes is also unclear: they correlate with tumor growth and invasion in murine models [44][45][46][47] but scarce observations associate a B cells signature to good prognosis in several human cancers [48][49][50]. Intratumoral NK cells have been reported to down regulate their activating receptors and to be associated to larger breast [51] and lung [28] tumors, but without clear impact on patients survival.…”
Section: The Immune Contexture Of the Tumor Microenvironment Has A Mamentioning
confidence: 99%